2013
DOI: 10.1111/jocn.12157
|View full text |Cite
|
Sign up to set email alerts
|

Psychometric properties of the Brazilian Portuguese versions of the 29‐ and 13‐item scales of the Antonovsky's Sense of Coherence (SOC‐29 and SOC‐13) evaluated in Brazilian cardiac patients

Abstract: This scale can be used in research and clinical practice in Brazil to assess nursing interventions aimed at decreasing stress during cardiac rehabilitation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
34
1
5

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 37 publications
(42 citation statements)
references
References 44 publications
2
34
1
5
Order By: Relevance
“…Nevertheless, recent research has focused on the study of the structure and content of sense of coherence. There are studies that support Antonovsky's idea of the sense of coherence as a general factor with three dimensions (Antonovsky, 1993;Drageset & Haugan, 2015;Klepp, Mastekaasa, Sørensen, Sandanger, & Kleiner, 2007;Rajesh et al, 2015;Söderhamn & Holmgren, 2004;Söderhamn, Sundsli, Cliffordson, & Dale, 2015;Spadoti Dantas et al, 2014). Söderhamn et al (2015) found evidence in a confirmatory factor analysis that confirmed the SOC-29 as one theoretical construct with three dimensions, comprehensibility, manageability, and meaningfulness.…”
Section: Construct Validitymentioning
confidence: 74%
“…Nevertheless, recent research has focused on the study of the structure and content of sense of coherence. There are studies that support Antonovsky's idea of the sense of coherence as a general factor with three dimensions (Antonovsky, 1993;Drageset & Haugan, 2015;Klepp, Mastekaasa, Sørensen, Sandanger, & Kleiner, 2007;Rajesh et al, 2015;Söderhamn & Holmgren, 2004;Söderhamn, Sundsli, Cliffordson, & Dale, 2015;Spadoti Dantas et al, 2014). Söderhamn et al (2015) found evidence in a confirmatory factor analysis that confirmed the SOC-29 as one theoretical construct with three dimensions, comprehensibility, manageability, and meaningfulness.…”
Section: Construct Validitymentioning
confidence: 74%
“…The cultural adaptation process was based on national and international technical literature, which supported the studies previously performed by researchers from the Group for Research on Rehabilitation and Quality of Life in which we operate, evidencing the face and content validities of the QASCI scale (7) . In a recent study that evaluated the psychometric properties of two experimental versions of the QASCI, the author found that the results of the percentage of each item showed extreme answers, that is, No/Never or Always, in 27 items (20) .…”
Section: Discussionmentioning
confidence: 88%
“…Most of the items had more than 50% of their answers to the extreme values of the answer scale ("No/Never" or "Always"), as occurred in 19 of the 32 items. Several participants marked value one ("No/Never") in the answer scale, making a total of 12 items (4,5,7,10,13,15,16,17,19,20,21,22 …”
Section: Validation Of the Qasci Adapted Version And Statistical Analmentioning
confidence: 99%
See 1 more Smart Citation
“…Numerous authors conclude that patients' SOC scores should be assessed to inform treatment decisions and interventions (Blom, Larsson, Serlachius, & Ingvar, 2010;Boman, Bjorvell, Langius, & Cedermark, 1999;Buchi et al, 1998;Ding et al, 2013;Drabe et al, 2015;Klang et al, 1996;Linnen et al, 2011;Matsuura et al, 2003;Myers et al, 2011;Norekval et al, 2010;Spadoti Dantas et al, 2014;Torrati et al, 2010). However, there is also some criticism to use the SOC for this purpose, since authors find its dimensions overlapping with other concepts such as anxiety or disease-related depression (Sack, Kunsebeck, & Lamprecht, 1997), suggesting that the SOC might be a proxy for mental health, well-being and functionality.…”
Section: Using the Soc As A Diagnostic Toolmentioning
confidence: 99%